Ensino por investigação e argumentação como promotores da alfabetização científica: análise do desenvolvimento de uma sequência de ensino investigativa em uma turma de ciências do ensino fundamental - Ramos, Rafael Alves (2020)
Currently, research in science education points to the need to provide individuals with scientific knowledge and at the same time make them capable of making decisions that also involve non-scientific issues. Several authors argue that Scientific Literacy - AC represents a parameter for science teaching from the perspective of learning scientific concepts, understanding the nature of Science and the relationship between Science, Technology, Society and Environment - CTSA. In this research we are concerned with the promotion of CA in teaching, for that we proposed the implementation of an Investigative Teaching Sequence - interdisciplinary SEI with characteristics of “doing science” in basic education. The proposed SEI presents activities that are based on the didactic modalities of investigation from the problematization of what is taught and from Argumentation, with the promotion of scientific thinking. The development of SEI involved students in a context of scientific research based on the use of numerous cultural resources. Among them, we highlight: speaking, writing and reading which are resources present in the Scientific Language - LC. We use data triangulation through video recording of episodes, the production of texts written by students in the activity notebooks and in a scientific report, aiming to analyze the presence of AC and Argumentation indicators. As results we identified: changes from alternative conceptions to scientifically structured concepts during the sequence of activities; use of scientific language and establishing a relationship of meanings about the phenomena in question; majority presence of CA indicators related to direct work with data or with the bases from which the subject or situation was understood; construction of logical and objective ideas; low prevalence or absence of certain AC indicators related to understanding situations; low frequency of Argumentation indicators in discursive interactions and little engagement in collective activity. With that, we consider that the presence of the AC and Argumentation indicators indicates that the AC is in process, and this process needs to remain in constant construction. We emphasize that one way to guide students in creating written arguments is to use an adapted layout. Regarding Teaching by Research and Argumentation, it is concluded that both present themselves as approaches and / or didactic modalities that privilege didactic situations with characteristics of scientific work. At this point, attention is drawn to the approximation of scientific culture with school, breaking with a culture of didactic practices without contextualization with science itself.